Estimation of vector propensity for Lettuce mosaic virus based on viral detectionin single aphids - Moreno, A.=700 1 Bertolini, E.; Olmos, A.; Cambra, M.; Fereres, A.
(En, Es)
Ilus., 41 ref.
Keywords: LECHUGA; VIRUS; APHIDIDAE; MYZUS PERSICAE; ESPAÑA; VIRUS NO PERSISTENTES; LETTUCE MOSAIC VIRUS; PULGONES